2023
DOI: 10.1088/1361-6498/acb366
|View full text |Cite
|
Sign up to set email alerts
|

CDMAM in digital mammography: contrast threshold measurements, achievable values and relation with dose

Abstract: The main goal of this study is to characterize threshold contrast values and average glandular dose (AGD) in mammography exams, as well as their relationship with acceptable (minimum quality values) and achievable values (desirable quality values) from the fourth edition of the EUREF protocol. Therefore, data from 84 mammography units of 6 different manufactures and 15 different models was gathered across Portugal during 2020 and 2021. The contrast measurements were obtained with a CDMAM 4.0 phantom. Within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Although constraining radiation doses received in medical diagnosis is important, where imaging modalities are used, the benefits of reducing doses have to be considered against the need to achieve adequate image quality. Trindade and Barreira (2023) examined this issue in the context of digital mammography using data from 84 mammography units from six different manufacturers comprising 15 different models. Amongst the tested units, six failed to comply with guidelines for acceptable performance.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although constraining radiation doses received in medical diagnosis is important, where imaging modalities are used, the benefits of reducing doses have to be considered against the need to achieve adequate image quality. Trindade and Barreira (2023) examined this issue in the context of digital mammography using data from 84 mammography units from six different manufacturers comprising 15 different models. Amongst the tested units, six failed to comply with guidelines for acceptable performance.…”
mentioning
confidence: 99%
“…Amongst the tested units, six failed to comply with guidelines for acceptable performance. Trindade and Barreira (2023) observed that many images were being produced with average glandular doses of less than the achievable glandular dose of 2.4 mGy. They concluded that their results show that it would be appropriate to increase the average glandular dose in many cases to achieve better image quality.…”
mentioning
confidence: 99%